2000
DOI: 10.1111/j.1348-0421.2000.tb02594.x
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella typhimurium Induces Apoptosis in Human Monocyte‐Derived Macrophages

Abstract: Salmonella species represent a leading cause of gastroenteritis worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
2
7
0
Order By: Relevance
“…It is unlikely that the differences observed were due to impaired infectivity, since the number of viable bacteria recovered per well after 30 min of infection was in the range of 1 ϫ 10 5 to 2 ϫ 10 5 for all strains tested. It has been demonstrated that S. enterica serovar Typhimurium is able to trigger apoptosis of infected macrophages (6,8,26,35,49,69). This process seems to play a key role also in elicitation of immune responses to Salmonella (67,69).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that the differences observed were due to impaired infectivity, since the number of viable bacteria recovered per well after 30 min of infection was in the range of 1 ϫ 10 5 to 2 ϫ 10 5 for all strains tested. It has been demonstrated that S. enterica serovar Typhimurium is able to trigger apoptosis of infected macrophages (6,8,26,35,49,69). This process seems to play a key role also in elicitation of immune responses to Salmonella (67,69).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that S. enterica serovar Typhimurium is able to trigger apoptosis of infected macrophages (6,8,26,35,49,69). This process seems to play a key role also in elicitation of immune responses to Salmonella (67,69). Since the intracellular survival of the mutant strain was reduced only in macrophages, not within epithelial cells, we decided to assess whether the capacity of the serovar Typhi ⌬gaiA mutant to stimulate programmed cell death was also affected.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to survive inside macrophages is associated with host adaptation in mammals and birds (1,7,20,25). In mammalian species, the intracellular survival of Salmonella in macrophages eventually leads to killing of the host macrophage in an apoptosis-like way (3,4,10,12,14,18,23,27). The pigeon strains were found in smaller numbers in the pigeon peritoneal macrophages after 24 h than the porcine strains.…”
mentioning
confidence: 99%
“…Some studies have shown that S. typhi and Salmonella enterica serovar Typhimurium (S. typhimurium) can mediate macrophage apoptosis. [6][7][8][9][10] The virulence of Salmonella strains in humans and other animals is frequently serovar specific. S. typhi causes typhoid fever only in humans, but no disease is associated with experimental infections in mice.…”
Section: Introductionmentioning
confidence: 99%